Effectiveness of Educational Intervention on Sanitation and Hygiene among Tribal School Children - Kandekar, Shivakumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Introduction: According to the WHO-UNICEF for sanitation and hygiene in 2020, 3.6 billion people do not have access to sanitation services, and 2.3 billion do not have access to hand wash facilities with soap and water.  Objectives: (i) To study the knowledge and awareness of sanitation and hygiene among Tribal school children. (ii) To assess the Effectiveness of sanitation and hygiene practices among tribal school children.  Methodology: An intervention study was conducted among tribal primary school children. Baseline data Regarding sanitation and hygiene facilities. Information was collected by using a Sanitation and hygiene checklist. Quasi-experimental research and Purposive sampling methods were used for the pre-test and post-test among 60 students of 4th & 5th classes in school. Initially, a pre-test was conducted by using the knowledge and awareness of sanitation and hygiene research questionnaire; after pre-test data collection, the sanitation and hygiene intervention module was implemented in the school; after the module intervention post-test was conducted by using the same questionnaire, and it was analysed through statistical techniques.  Result: The intervention module is based on students' and teachers‟ participation, sanitation, and hygiene-related themes. After intervention study brings changes and improvement in the tribal school knowledge and awareness of sanitation and hygiene status behavioural change, and attitude in Tribal school children. Conclusion: Implementation of sanitation and hygiene in schools is going to be fruitful school health. Children's health and hygiene behaviour, improving handwashing behaviour, and food hygiene inculcated after the Pandemic COVID-19-time resulted in sustaining the character during childhood school.